The effectiveness of project management practices and performance in the beverage industry in Ghana: A case of coca cola company - Batie, Gilbert Dome-Iire (2021)
A thesis submitted to the Department of Construction Technology and Management, College of Art and Built Environment in partial fulfillment of the requirement for the Degree of Master of Science.